2017
DOI: 10.1002/ep.12810
|View full text |Cite
|
Sign up to set email alerts
|

New thermodynamic analysis and optimization of performance of an irreversible diesel cycle

Abstract: In this study, an irreversible Diesel cycle is investigated based on entransy method and optimization conducted by considering various scenarios. Entransy expressed as a heat transfer potential of a subject and it has begun to investigate as a new thermodynamic assessment parameter. This paper presents thermodynamical study of an irreversible Diesel cycle in order to optimize its performance. Moreover, four different strategies in the process of multiobjective optimization are proposed, and the outcomes are as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 103 publications
(163 reference statements)
1
2
0
Order By: Relevance
“…The multiobjective optimization of the system was performed using NSGA‐II considering generator, evaporator, and condenser temperatures as design variables. Similar multiobjective optimization studies are exercised in the literature 20–22 using NSGA‐II and improved results were observed by the authors.…”
Section: Introductionsupporting
confidence: 69%
“…The multiobjective optimization of the system was performed using NSGA‐II considering generator, evaporator, and condenser temperatures as design variables. Similar multiobjective optimization studies are exercised in the literature 20–22 using NSGA‐II and improved results were observed by the authors.…”
Section: Introductionsupporting
confidence: 69%
“…Ahmadi et al used NSGA-II and TOPSIS and LINMAP to solve the optimum solution in refrigeration systems (Ahmadi et al, 2016a(Ahmadi et al, , 2016b. More recently, Ahmadi et al used NSGA-II and TOPSIS, LINMAP, and Fuzzy Bellman-Zadeh models to solve the optimum solution in hydrogen production system, and Diesel cycle (Ahmadi et al, 2018a(Ahmadi et al, , 2018b. Beyond the application of genetic algorithms together with TOPSIS, Chen et al ( 2019) developed a hybrid atmospheric pollutant concentration forecasting model based on a particle swarm optimization (PSO) algorithm, the support vector machine (SVM) method, and a Kmeans clustering algorithm, conducting a case study in Beijing.…”
Section: The Applications Of a Genetic Algorithm Together With Topsismentioning
confidence: 99%
“…Multiobjective optimization is also studied to find the optimum solution for environmental effects in various thermal systems . Further, the multiobjective optimization of the various system like refrigerators, heat engine, cryogenic cycle, irreversible Brayton cycle, irreversible Diesel cycle, Stirling engine, heat pump, and power cycles have been carried out using evolutionary algorithms.…”
Section: Introductionmentioning
confidence: 99%